2018
DOI: 10.25165/j.ijabe.20181102.2788
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of drying conditions and components to reduce wall sticking during spray drying of infant formula milk

Abstract: Abstract:Wall sticking, which greatly reduces productivity and product quality, has been a big challenge of spray drying. Structure of drying tower and atomizer, as well as drying conditions are the main influencing factors. This research explored the possibility to reduce wall sticking by optimizing drying conditions and components to obtain higher recovery rate of powdered infant formula milk (PIFM). Response surface experimental results indicated that inlet air temperature (T), feed concentration (C), feedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 17 publications
0
10
0
1
Order By: Relevance
“…For example, Lin and colleagues demonstrated that increased recovery for infant formula was obtained by operating the spray drying at higher temperature (160°C) and lower feed rate (4 mL/min). [9] As presented in Table 2, skimmed camel milk powders were produced with total solids content in the range of 92-98% (w/w) in which most frequent values were in the range of 95-97% (w/w) with a moisture contents in the range of 3-5 (% w/w). This would be convenient for storage in commercial storage conditions.…”
Section: Yield and Composition Of Spray-dried Skimmed Camel Milk Powdersmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, Lin and colleagues demonstrated that increased recovery for infant formula was obtained by operating the spray drying at higher temperature (160°C) and lower feed rate (4 mL/min). [9] As presented in Table 2, skimmed camel milk powders were produced with total solids content in the range of 92-98% (w/w) in which most frequent values were in the range of 95-97% (w/w) with a moisture contents in the range of 3-5 (% w/w). This would be convenient for storage in commercial storage conditions.…”
Section: Yield and Composition Of Spray-dried Skimmed Camel Milk Powdersmentioning
confidence: 99%
“…For example, Lin and colleagues demonstrated that increased recovery of total solids for infant formula was obtained by operating the spray drying at higher temperature (160°C) and lower feed rate (4 mL/min). [9]…”
Section: Yield Of Skimmed Camel Milk Powdersmentioning
confidence: 99%
See 2 more Smart Citations
“…Fenomema menempelnya bahan kering pada dinding spray dryer disebut dengan lengket dinding (wall sticking). Menurut Lin et al, (2018) salah satu tantangan besar dalam proses spray drying adalah terjadinya fenomena lengket dinding yang dapat menurunkan produktivitas dan kualitas produk secara signifikan. Faktor utama yang memengaruhi kelengketan bahan yang memiliki gula tinggi adalah higroskopisitas, solubilitas, titik lebur, dan suhu transisi gelas.…”
Section: Rendemenunclassified